2010
DOI: 10.1016/s0924-9338(10)71294-3
|View full text |Cite
|
Sign up to set email alerts
|

P03-240 - Psychological, Environmental Or Physical Factors, Which Is The First Cause In Tendency To Addiction?

Abstract: The aim of the research is to test this question what is the first cause of addiction? Psychological, Environmental or Physical causes. Method: 80 addicted people were randomly selected and Abuse Drug Assessment Inventory (ADAI) was administered on them. Chi Square formula was used to analyze the results. Results: Findings showed 55 percent of tendency to addiction was psychological. Also more analyzing showed 65 percent of continuing causes of addiction were psychological factors such as fear, anxiety, sorrow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Other research studies were found which also supported the idea of fear and addiction being linked physiologically [14][15][16] . Fear has been shown to be physiologically related to addiction in the prefrontal and orbitofrontal cortexes of the brain, but also has many psychological components in the addicted person.…”
Section: Discussionsupporting
confidence: 59%
“…Other research studies were found which also supported the idea of fear and addiction being linked physiologically [14][15][16] . Fear has been shown to be physiologically related to addiction in the prefrontal and orbitofrontal cortexes of the brain, but also has many psychological components in the addicted person.…”
Section: Discussionsupporting
confidence: 59%